2003
DOI: 10.1002/tox.10094
|View full text |Cite
|
Sign up to set email alerts
|

Tannery wastewater characterization and toxicity effects on Daphnia spp.

Abstract: Tannery wastewater contains large quantities of organic and inorganic compounds, including toxic substances such as sulfides and chromium salts. The evaluation of wastewater quality in Chile nowadays is based on chemical specific measurements and toxicity tests. The goal of this research was to characterize tannery wastewater and to relate its physical/chemical parameters with its acute toxicity effect on Daphnia pulex. To distinguish the most important toxic compounds, physical/chemical techniques were applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
0
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(82 citation statements)
references
References 15 publications
(15 reference statements)
4
68
0
4
Order By: Relevance
“…Tannery wastewater contains large amounts of pollutants including sodium chloride, sodium sulfate, toxic metallic compounds of chromium, and various other organic and inorganic compounds [1][2][3][4]. The tanning industries discharge their effluents into nearby lands or rivers, damaging the environmental compartments and thus causing serious harm to human health [2,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Tannery wastewater contains large amounts of pollutants including sodium chloride, sodium sulfate, toxic metallic compounds of chromium, and various other organic and inorganic compounds [1][2][3][4]. The tanning industries discharge their effluents into nearby lands or rivers, damaging the environmental compartments and thus causing serious harm to human health [2,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Cosmopolitan Daphnia magna (Straus 1820) is widely used as an indicator for freshwater evaluation (Cooman et al 2003;Xavier et al 2005;Reyes et al 2009), although Daphnia obtusa (Kurz 1874) is the principal species that survives in many aquatic ecosystems, including the Chilean ecosystem. Previous evidence for chronic activity, such as comparative study of the sensitivity for D. magna and D. obtusa, show the effect of exposure to inorganic and organic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…This sludge showed higher amount of iron and lower Tchobanoglous et al 2003). Also, nitrogen content was lower than data published for digested sludge from a conventional wastewater treatment plant (Tchobanoglous et al 2003), but higher than found in the tannery effluent composition (Cooman et al 2003). Reported total dry solids are lesser compared with those present in the sludge (between 76 and 98 % lower).…”
Section: Sludgementioning
confidence: 60%